2003
DOI: 10.1080/01443610310000100114
|View full text |Cite
|
Sign up to set email alerts
|

Cervical cytology in an urban population in Lagos, Nigeria

Abstract: Eight hundred and eighty-four consecutive women had cervical smears in a clinic in Lagos, Nigeria between September 1998 and 31 August 1999. Mean age was 36.6 - 11.6 years (range 16-81 years); 93.7% were first-time screening. Three hundred and twenty-five (36.5%) smears were normal, inflammatory smears 52.7%, mild dyskaryosis 2.4%, moderate dyskaryosis 1.5%, severe dyskaryosis 0.3% and probable malignancy (malignant cells) 0.8%. Abnormal smears were higher in symptomatic cases compared with asymptomatic cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 7 publications
3
15
1
Order By: Relevance
“…Though this prevalence is considerably higher than a range of 5.0–6.8% [23][25] reported among HIV negative women in Nigeria, the higher prevalence was used because of the large proportion of HIV positives in this study. The minimum sample size for a statistically meaningful deduction was determined using the formula: N = Zα 2 P (1-P)/d2, where Zα is the Z statistic for a 95% confidence level, N is the sample size, p is the prevalence of cervical cell abnormality, and d is the precision.…”
Section: Methodsmentioning
confidence: 69%
See 1 more Smart Citation
“…Though this prevalence is considerably higher than a range of 5.0–6.8% [23][25] reported among HIV negative women in Nigeria, the higher prevalence was used because of the large proportion of HIV positives in this study. The minimum sample size for a statistically meaningful deduction was determined using the formula: N = Zα 2 P (1-P)/d2, where Zα is the Z statistic for a 95% confidence level, N is the sample size, p is the prevalence of cervical cell abnormality, and d is the precision.…”
Section: Methodsmentioning
confidence: 69%
“…Anorlu et al [23], Durowede et al [24] and Pimentel et al [25] in their separate studies reported lower SIL prevalence of 5.0%, 5.0% and 6.8%, respectively, in Lagos, Okene and Olufadi in Nigeria. The difference between the findings of these studies and our study may be due to the large proportion of HIV positive persons in our cohort.…”
Section: Discussionmentioning
confidence: 87%
“…There is no evidence from randomize control trials to answer this question [4,5]. Variations in study design and statistical analysis, study locations (developed or undeveloped countries) are the reasons beyond this dilemma [1,6,7]. Furthermore PCB shows multiple etiologies in which most are benign such as cervicitis or cervical polyps.…”
Section: Introductionmentioning
confidence: 89%
“…This was consistent in the literature, 60% of naturally menstruating women with PCB will have spontaneous resolution of symptoms within six months. Half of these women will find resolution after two years [7].…”
Section: Commentsmentioning
confidence: 98%
See 1 more Smart Citation